Study of Cost-benfit Analysis of Hydroponic Vegetables With Nutrient Film Technique Systems in Indonesia - Sukendar, Ni Made Classia; Dewi, Ni Luh Made Indah Murdyani (JURNAL MANAJEMEN AGRIBISNIS; Vol 11 No 01 (2023): Jurnal Managemen AgribisnisDO - 10.24843/JMA.2023.v11.i01.p05, 2023)
This study compares the financial feasibility studies of several NFT hydroponic vegetable farming systems in Indonesia. Studies on financial feasibility are important to be carried out in order to be taken into consideration in making decisions in a farming business. The method used in this study is a literature study for secondary blood collection from several journals consisting of IRR, NPV, and Net B/C Ratio values. Four NFT system hydroponic vegetable farms were reviewed in the study, all of which were related to cost-benefit analysis including the NFT system hydroponic vegetable farms located in Bogor, Ciamis, East Jakarta, and Banjarmasin. This study resulted in the NFT hydroponic vegetable farming in Bogor, precisely at PT. Cifa Indonesia has an NPV value of Rp. 33,478,083, an IRR of 52%, and a Net B/C Ratio of 5.56. This shows that the hydroponic vegetable farming PT. Cifa Indonesia in Bogor is more profitable to develop than other NFT system hydroponic farming. The results of this study are expected to be a reference for hydroponic vegetable farming developers with the NFT system.